L’azione degli Orti botanici per l’introduzione di piante utili o scientificamente importanti (Altre Modernità, 2013)
The Botanical Gardens have always played a central role in the transfer of plants, aimed, among other objectives, to scientific research and economic use. On this issue the Botanical Gardens of Florence, Meise (Belgium) and Madrid thanks to a European Partnership, as part of the Lifelong Learning Programme, aimed at creating new educational tools in the field of botanical. The three Botanical Gardens, so different for origine, history, location, have found in the history of the scientific expeditions of their home countries, the matter common to build, each in its own reality, a self-guided trail. The attention has been focused on plants which are sgnificant for the scientific research and for economic use, introduced in Europe from the eighteenth century till to the present day. The plants chosen from the three gardens - including Amorphophallus titanum and some species within the genus Coffea, Dahlia and Passiflora - represent the link who joins the history of explorations and the new challenges that the Botanical Gardens facing in the complex modern reality.